Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 10 - Review: 144



Work Step by Step

$\sqrt[3] {-x^{12}y^{3}}$ =$(-1\times x^{12}\times y^{3})^{\frac{1}{3}}$ =$(-1)^{\frac{1}{3}}\times(x^{12})^{\frac{1}{3}}\times(y^{3})^{\frac{1}{3}}$ =$-1\times(x^{4})\times(y^{1})$ =$-x^{4}y^{1}$ =$-x^{4}y$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.